Bilateral total hip replacement in arthrogryposis multiplex congenita. (25th November 2015) - Dalton, David Michael; Magill, Paul; Mulhall, Kevin James
Abstract : The authors present a case of bilateral total hip replacements (THRs) in a 56-year-old patient with arthrogryposis multiplex congenita (AMC). The considerations for the perioperative period and the outcome are discussed. Preoperative planning included an anaesthetic review and availability of fiberoptic intubation due to poor mouth opening. Perioperatively, contractures can make positioning and exposure difficult but in this case a standard posterior approach was taken. Particular attention was given to soft tissue balancing given the theoretical risk of dislocation. There were no perioperative complications. Postoperatively there has been improvement in pain and hip scores but the patient has failed to return to work. Objective improvements in range of motion (ROM) have not been made. This experience suggests THR is a safe and effective treatment for osteoarthritic hip pain in patients with AMC but patients should be informed that ROM is unlikely to improve.